Optimization of technical training of ice-hockey players aged 8-17 years - Girdauskas, G.; Kazakevièius, R. (Education. Physical training. Sport, 2013)
Research background and hypothesis. Training models in athlete training have already been determined by sport researchers (Hellard et al., 2006. The programme that has been developed and tested by one alternative experiment is targeted to optimize the purposeful technical training for 8-17-year-old ice hockey players. Research aim was to determine technical training models. Research methods. A long-term experiment of one alternative was carried out involving subjects from 8 to 18 years in 2000-2010. The programmes for technical training were developed with regard to the time ratio, measures taken and recommendations of foreign experts. Later the programmes have been adjusted to the results obtained. The following tests have been used for evaluation of the skating technique: to evaluate specific skills - forward and backward skating; to evaluate the puck control - manoeuvre skating driving the puck and without the puck. Research results. Analysis of the results in the initial training period shows that the greatest improvement in the results has been registered in manoeuvre skating driving the puck - 11.6%, and in backward skating - about 8%. A significant improvement in the results of the basic training period has been observed in backward skating - 7% as well as in 30 m standing skating - 6.3%. In the special training period a more marked increase in the results has been registered in backward skating - 5.2% as well as in 30 m standing skating - 3.8%. Discussion and conclusions. This is due to the lack of special skills and a complex biomechanical structure of the performance of the technical action. Sport performance was influenced by adolescent developmental patterns, and the optimal adjustment of the programme, taking into account the initial and basic training period analysis. Results of the present research allow us to conclude that 1) Athletes` training programmes, taking into account the recommendations, were effective. 2) The greatest improvement in the results was registered within the 1st and 2nd stages of athletes` training. We believe that this is due to a complex biomechanical structure of the performance of the technical action. After the improvement, the growth of the results slows down. 3) Time ratio for technical training is distributed in the following way: 1st stage - 55-53%, 2nd stage - 50-48% and 3rd stage - 47-44%.